1998
DOI: 10.1159/000054308
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pulsed High-Frequency Electromagnetic Fields on the Neuroendocrine System

Abstract: The influence of pulsed high-frequency electromagnetic fields emitted from a circularly polarized antenna on the neuroendocrine system in healthy humans was investigated (900 MHz electromagnetic field, pulsed with 217 Hz, average power density 0.02 mW/cm2). Nocturnal hormone profiles of growth hormone (GH), cortisol, luteinizing hormone (LH) and melatonin were determined under polysomnographic control. An alteration in the hypothalamo-pituitary-adrenal axis activity was found with a slight, transien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
2
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 19 publications
3
42
2
2
Order By: Relevance
“…Long-term magnetotherapy influences the circadian profile of cortisol secretion, a decrease of cortisol concentration after 3 weeks of applications at 4:00 p.m. was observed [33]. Mann et al [34] reports that in humans exposed to high frequency magnetic field, 900 Hz, pulsating at 217 Hz (the frequency of the field similar to magnetostimulation), there appears to be a slight increase in the concentration of cortisol during acute exposure, which is sustained for about an hour after the application. In a 24-hour long-term exposure, the statistically significant changes in cortisol secretion were not noted [34], just as in Kurokawa et al [35] and Randon et al [36].…”
Section: Resultsmentioning
confidence: 99%
“…Long-term magnetotherapy influences the circadian profile of cortisol secretion, a decrease of cortisol concentration after 3 weeks of applications at 4:00 p.m. was observed [33]. Mann et al [34] reports that in humans exposed to high frequency magnetic field, 900 Hz, pulsating at 217 Hz (the frequency of the field similar to magnetostimulation), there appears to be a slight increase in the concentration of cortisol during acute exposure, which is sustained for about an hour after the application. In a 24-hour long-term exposure, the statistically significant changes in cortisol secretion were not noted [34], just as in Kurokawa et al [35] and Randon et al [36].…”
Section: Resultsmentioning
confidence: 99%
“…Chronic application of 2.9 mT, 50 Hz EMF lowered the level of LH, whereas no changes were observed after chronic exposure to 25-80-µT, 200 Hz EMF [42] and acute exposure to 10 µT, 40 Hz (continuous or intermittent) [41] or to GSM-standard [32]. Woldanska-Okonska et al [42] observed a decrease in prolactin concentrations following chronic application of EMF (25-80 µT, 200 Hz and 2.9 mT, 40 Hz, for 3 weeks) whereas acute exposure to 1 µT, 50 Hz [30] or 20 µT, 50 Hz did not influence the concentrations of this hormone [39].…”
Section: Electromagnetic Fields and Pituitary Hormonesmentioning
confidence: 88%
“…No significant effects of EMF on the secretion of growth hormone and FSH have been found [32,39,41,42] (Table 2). Chronic application of 2.9 mT, 50 Hz EMF lowered the level of LH, whereas no changes were observed after chronic exposure to 25-80-µT, 200 Hz EMF [42] and acute exposure to 10 µT, 40 Hz (continuous or intermittent) [41] or to GSM-standard [32].…”
Section: Electromagnetic Fields and Pituitary Hormonesmentioning
confidence: 94%
See 2 more Smart Citations